Efektivitas Lembar Kerja Siswa (LKPD) pada Mata Pelajaran IPA Berbasis Model Inkuiri di SD Kelas V - Putri, Risna Estuning; Nurhayati, Nurhayati; Pramudiyanti, Pramudiyanti; Dewi, Pramita Sylvia (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to evaluate the effectiveness of inquiry-based Student Worksheets (LKPD) in science subjects for fifth-grade elementary students. The research design used is a pre-experimental design, starting with the validation of the LKPD by experts. Then, students were given a pre-test to measure their initial knowledge. Subsequently, the guided discovery-based LKPD was used by the students during several learning sessions. After using the LKPD, a post-test was conducted to measure the improvement in student learning outcomes. Additionally, interviews were conducted with teachers and students to gather feedback on the use of the LKPD. The results showed that the average student learning outcome after using the guided discovery-based LKPD reached 72.2, with an average increase of 14.72 compared to the pre-test. Data analysis indicated that the calculated t-value was 8.626, significantly higher than the table value of 0.000000008. This significant difference demonstrates that the use of the inquiry-based LKPD is effective in improving student learning outcomes.In conclusion, the inquiry-based LKPD in science subjects for fifth-grade students at SDN 2 Adijaya has proven to be effective in enhancing student learning outcomes, as evidenced by the significant increase in scores following the use of the LKPD.